1995
DOI: 10.1136/jnnp.59.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion and psychometric testing in military amateur boxers and controls.

Abstract: Boxers who had fought fewer bouts had a tendency to perform better at psychometric tests than those boxers who had fought more bouts. Tc-99m HMPAO SPECT cerebral perfusion scanning showed that controls had less aberrations in cerebral perfusion than the boxers.In conclusion, significant differences were shown in two neurophysiological variables between young amateur sportsmen who box and those who do not. The long term effects of these findings remain unknown.(7 Neurol Neurosurg Psychiatry 1 995;59:368-374)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…The most common abnormality in patients with postconcussive symptoms was hypoperfusion of the basal ganglia (50%) or frontal lobes (46%) (1). Studies of asymptomatic boxers have also demonstrated reduced cerebral perfusion in the frontal and temporal lobes on SPECT scanning (29). However, SPECT imaging has been poorly correlated with performance in neuropsychiatric tests (19,58).…”
Section: Imaging Studiesmentioning
confidence: 99%
“…The most common abnormality in patients with postconcussive symptoms was hypoperfusion of the basal ganglia (50%) or frontal lobes (46%) (1). Studies of asymptomatic boxers have also demonstrated reduced cerebral perfusion in the frontal and temporal lobes on SPECT scanning (29). However, SPECT imaging has been poorly correlated with performance in neuropsychiatric tests (19,58).…”
Section: Imaging Studiesmentioning
confidence: 99%
“…4 Nevertheless, the evidence for TBI in amateur boxers is controversial. [5][6][7] SWI is a new technique for the evaluation of DAI associated with punctate hemorrhages in brain parenchyma. The aim of our study was to determine the prevalence of cerebral microhemorrhages in amateur boxers compared with nonboxers by using SWI and to evaluate the sensitivity of SWI compared with T2 FSE and T2*GE sequences for assigning the number of microhemorrhages in amateur boxers.…”
mentioning
confidence: 99%
“…30 However, some researchers have reported neuropsychological decrements 31 or temporary adverse effects on subjective symptoms 32 associated with heading the soccer ball. Commonsense and empirical evidence suggest that a career in boxing will probably result in obvious [33][34][35][36][37][38] or subtle 39 damage to the structure and function of the brain. However, a least one prospective study 40 and several other studies have not confirmed this 41 42 or have reported mixed or equivocal results.…”
mentioning
confidence: 99%